Patient-initiated follow-up after treatment for low risk endometrial cancer: a prospective audit of outcomes and cost benefits. Issue 8 (5th May 2020) - Coleridge, Sarah; Morrison, Jo
Abstract : Objective: Recurrence of low-risk endometrioid endometrial cancer is rare, and traditional hospital follow-up has a cost to both the patient and the healthcare system, without evidence of benefit. We examined the uptake of patient-initiated follow-up, pattern of recurrences, and survival for women following surgical treatment of low-risk endometrial cancer and compared estimated costs with hospital follow-up. Methods: This study was a prospective audit of outcomes following implementation of a patient-initiated follow-up policy in a UK-based gynecological cancer center for women with low-risk endometrial cancer treated surgically (International Federation of Gynecology and Obstetrics (FIGO) stage 1A, G1-2) from January 2010 to December 2015. Women were identified following multidisciplinary team meetings and data were collected from the electronic cancer register, paper, and electronic clinical records. Health service costs were calculated based on standard tariffs for follow-up appointments; patient costs were estimated from mileage traveled from home postcode and parking charges. Progression-free survival and overall survival were assessed. Estimated financial costs to the health service and patients of hospital follow-up were compared with actual patient-initiated follow-up costs. Results: A total of 129 women were offered patient-initiated follow-up (declined by four; accepted by another 11 after hospital follow-up for 6 months to 3.5 years) with median follow-up of 60.7 months (range 1.4–109.1 months). Ten women recurred: four vaginal vault recurrences (all salvaged), three pelvic recurrences (all salvaged), and three distant metastatic disease (all died). Five-year disease-specific survival was 97.3%. Ten women in the cohort died: three from endometrial cancer and seven from unrelated causes. The cost saving to the health service of patient-initiated follow-up compared with a traditional hospital follow-up regimen was £116 403 (median £988.60 per patient, range £0–£1071). Patients saved an estimated £7122 in transport and parking costs (median £57.22 per patient, range £4.98–£147.70). Conclusion: Patient-initiated follow-up for low risk endometrial cancer has cost benefits to both health service and patients. Those with pelvic or vault recurrence had salvageable disease, despite patient-initiated follow-up.